Supportive and Palliative Care and Quality of Life in Oncology - Abdul Rasool Hassan, Bassam (IntechOpen, 2023)
This book examines supportive and palliative care and quality of life in cancer patients. Chapters address such topics as anxiety, depression, and delirium in terminally ill cancer patients, ethics in palliative care, palliative care medications, assisted suicide and euthanasia, and much more.